DIPLOMATIC IMMUNITY AND OPPORTUNITY - Ahmedov Azimjon; Ahmadjonova Gulorom Alijon kizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: Diplomatic Immunity and Diplomat's Rights and Vienna Convention on Diplomatic Laws are detailed in the following article